Monarch of the glen. Series 3 [videorecording (DVD)] - Brint, Simon; Mackenzie, Compton, 1883-1972 (BBC Video, 2005)
Archie continues his struggles to make Glenbogle a success and sort out his complicated love live. Includes all eleven episodes from the third series, Richard Brier's last.